Exploring climate smart agriculture in Turkey: Enhancing food security and sustainable practices for the reduction of CO₂ emissions - Nawaz Khan; Wang Jie (PLoS ONE, 2026)
Climate-smart agriculture entails the reduction of CO₂ emissions, adaptation and modification of technology to enhance resilience to climate change, and sustainable increase of incomes. This study evaluates the effectiveness of smart agricultural practices in Turkey, which significantly impact food security and mitigate CO₂ emissions. The decoupling technique was implemented to estimate the portfolio returns and examine their correlation with climate-smart agriculture and CO₂ emissions over the anticipated period of 1992–2023. The decoupling technique was implemented to accomplish the two primary objectives. First, it is employed to calculate the percentage change in portfolio returns that is linked to both high and low weighted risk allocations. Second, it enables the prediction of CO₂ emissions levels for the next five years, which are influenced by sustainability practices and food security fluctuations. A corresponding difference in the efficacy of climate-smart agriculture has been demonstrated in the agricultural context by a percentage change in continuous, single aeration, and multiple aeration practices. The estimated results suggest that the decoupling trend in portfolio returns is significantly influenced by factors such as rice cultivation, field rise, and soil management, which also contribute to the highest weighted risk. Additionally, this factor consistently shows the highest weighted importance in determining overall portfolio returns, as it exhibits the largest marginal effects. Consequently, this investigation substantiates the detrimental influence of these variables on CO₂ emissions. Turkey’s sustainable smart agriculture process is essential for the efficient expansion of the economy, as it integrates climate change considerations into current policies and initiatives and reinforces the policy indicator of economic consideration with environmental protection in terms of CO₂ emissions.